Effect of Season on Diet Composition, Dry Matter Intake and Digestibility in Adult Sheep Grazed on Sub-Alpine Pastures of Kashmir Valley - Mir, Shahid H.; Haider, A.; Ahmed, A.; Ganai, A.M.; Afzal, Yasir (Indian Journal of Animal Nutrition, 2018)
The present study was designed to analyzes the seasonal variations in diet composition, nutrient intake and digestibility of sub-alpine pastures of Kashmir valley in mature sheep. The experiment was conducted in two seasons of summer (June) and autumn (October) at two locations (MRCSG, Shuhama, Location-I and SBF, Dachigam, Location-II) having different vegetative covers. The apparent digestibility of most of the nutrients was higher (P<0.05) in summer than in autumn season. The ME, TDN and DCP contents of the summer pastures were higher (P<0.05) than the autumn pastures at both locations. Dry matter intake from the summer pastures was higher than the winter pastures at both locations and their corresponding digestibilities also followed the same trend. Calcium intake was higher (P<0.05) in summer at location-I compared to location-II. However, P intake (g/d) from both pastures was higher (P<0.05) in summer than autumn season. The TDN intake (g/d) was deficient by 7% and ME intake (Mcal/d) by 5% in comparison to ICAR feeding standard (2013) in summer season at location-I while in autumn season the deficiency increased to 44 and 43%, respectively. Location-II offered adequate nutrients to animals in summer season while in autumn season the deficiency of 24% in TDN intake (g/d) and 22% in ME intake (Mcal/d) was observed. The DCP intake (g/d) was deficit by 12% at location- I in the autumn season while in summer season it was adequate at both the locations. Hence, the pastures at both the locations were deficient in energy especially in autumn season.